Exploring the isoform selectivity of TGX-221 related pyrido[1, 2-a]pyrimidinone-based Class IA PI 3-kinase inhibitors: Synthesis, biological evaluation and molecular modelling. Issue 13 (1st July 2015) - Marshall, Andrew J.; Lill, Claire L.; Chao, Mindy; Kolekar, Sharada V.; Lee, Woo-Jeong; Marshall, Elaine S.; Baguley, Bruce C.; Shepherd, Peter R.; Denny, William A.; Flanagan, Jack U.; Rewcastle, Gordon W.
Graphical abstract: Abstract: A novel series of TGX-221 analogues was prepared and tested for their potency against the p110α, p110β, and p110δ isoforms of the PI3K enzyme, and in two cellular assays. The biological results were interpreted in terms of a p110β comparative model, in order to account for their selectivity towards this isoform. A CH2 NH type linker is proposed to allow binding into the specificity pocket proposed to accommodate the high p110β-selectivity of TGX-221, although there was limited steric tolerance for substituents on the pendant ring with the 2-position most favourable for substitution.